Determination of phylogenetic and molecular characteristics of three Malaysian ginger cultivars (zingiber officinale roscoe) using microsatellite DNA - Mahdi, Harith Jameel; Budi Muljono, Julia Retno Andayani; Aziz, Ishak (Penerbit Universiti Sains Malaysia, 2013)
Three Malaysian ginger cultivars (Bukit Tinggi, Tanjung Sepat and Sabah) were collected and examined for genetic polymorphisms using microsatellite DNA primers. The single microsatellite oligonucleotide primers (CATA)5 (GATA)5 and (GAC)6 were used in polymerase chain reactions (PCRs). These PCR reactions produced 7 polymorphic bands with an avarage of 2.334 polymorphic bands per primer, leading to an average polymorphism rate of 17.9%. Cluster analysis revealed 87.50% similarity between Bukit Tinggi and Tanjung Sepat, 64.27% similarity between Bukit Tinggi and Sabah and 56.25% similarity between Tanjung Sepat and Sabah. DNA sequencing of the polymorphic PCR products of Tanjung Sepat ginger revealed the characteristic features of a putative new gene: a core promotor sequence, an enhancher and a transcription start site. Cluster analysis using the unweighted pair group method with arithmetic average (UPGMA) was used to construct a phylogenetic tree, which indicated that Bukit Tinggi ginger is genetically more closely related to Tanjung Sepat ginger than to Sabah ginger. Based on the results of this study, we concluded that there is genotypic variation among ginger cultivars, and the microsatellite DNA primers described here are useful for detecting polymorphic DNA in Malaysia gingr cultivars. Additionally, these microsatellite DNA primers may be used as molecular markers for discriminating among selected Malaysian gingr cultivars.